(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article examines the benefits and effectiveness of incorporating board games into English as a Second Language (ESL) classes as a tool for enhancing language learning. By engaging students in interactive and fun gameplay, board games provide opportunities for vocabulary development, grammar practice, communication skills, critical thinking, problem solving and social interaction. The article highlights how board games can create a dynamic and engaging learning environment that promotes language acquisition and promotes cultural understanding among students.